2018
DOI: 10.21769/bioprotoc.2898
|View full text |Cite
|
Sign up to set email alerts
|

Preserve Cultured Cell Cytonemes through a Modified Electron Microscopy Fixation

Abstract: Immunocytochemistry of cultured cells is a common and effective technique for determining compositions and localizations of proteins within cellular structures. However, traditional cultured cell fixation and staining protocols are not effective in preserving cultured cell cytonemes, long specialized filopodia that are dedicated to morphogen transport. As a result, limited mechanistic interrogation has been performed to assess their regulation. We developed a fixation protocol for cultured cells that preserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Depth analysis of the mCherry-Mem signal revealed that cytoneme-like projections originated from portions of the cell membranes that were not in contact with the growth surface ( Figure 1A’–A’’’, B’’ ). The small diameter, long lengths, and growth patterns of these extensions are consistent with the documented characteristics of cytonemes, indicating NIH3T3 cells and MEFs can be used to interrogate the specialized filopodia ( Bodeen et al, 2017 ; Hall and Ogden, 2018 ; Kornberg and Roy, 2014 ; Ramírez-Weber and Kornberg, 1999 ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Depth analysis of the mCherry-Mem signal revealed that cytoneme-like projections originated from portions of the cell membranes that were not in contact with the growth surface ( Figure 1A’–A’’’, B’’ ). The small diameter, long lengths, and growth patterns of these extensions are consistent with the documented characteristics of cytonemes, indicating NIH3T3 cells and MEFs can be used to interrogate the specialized filopodia ( Bodeen et al, 2017 ; Hall and Ogden, 2018 ; Kornberg and Roy, 2014 ; Ramírez-Weber and Kornberg, 1999 ).…”
Section: Resultssupporting
confidence: 66%
“…To interrogate cytoneme-based SHH transport in mammalian systems, NIH3T3 cells and mouse embryonic fibroblasts (MEFs) expressing SHH plus the membrane marker mCherry-Mem (mCherry fused to the first 20 residues of neuromodulin) were fixed using the MEM-fix technique, and then examined by confocal microscopy ( Figure 1A–B’’ ; Bodeen et al, 2017 ; Hall and Ogden, 2018 ). Image analysis of the mCherry-Mem signal in SHH-expressing cells revealed long extensions from both NIH3T3 cells and MEFs that reached around and over neighboring cells ( Figure 1A–B’’ ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence and imaging. Cell fixation and staining were performed using MEM-fixation protocols (6). The following antibodies and dilutions were used: rabbit anti-SHH (H-160) ( Fluorescence Recovery After Photobleaching (FRAP).…”
Section: Methodsmentioning
confidence: 99%
“…For quantification we defined cytonemes in cultured cells as cellular projections approximately < 200 nm in diameter, with a minimum length of 10 µm. Any cellular protrusions that originated from the basal surface of the cell and maintained continuous contact with the coverslip were excluded from analysis(6). For live imaging cytonemes were identified as motile protrusions, capable of elongation with the exception if a cytoneme was in contact with a nearby cell body or other cells' cytonemes.…”
mentioning
confidence: 99%